Optimization study on the effects of shear rate and concentration of inhibitor on wax and asphaltene deposition from crude oil using copolymer and aromatic compounds - S. M., Anisuzzaman; D., Krishnaiah; Mariani, Rajin; Sariah, Abang; N. M., Ismail; M., Madsah (The Malaysian Institute of Chemistry (Institut Kimia Malaysia), 2019)
In this study, the effects of shear rate and an ethylene-vinyl acetate (EVA)-based wax inhibitor towards the viscosity of crude oil was investigated. The viscosity of crude oil decreased when the shear rate increased and the most effective shear rate (in terms of rotational speed) was 100 rpm, which could reduce viscosity as high as 62.96 compared to the lowest shear rate applied (20 rpm). The EVA-based wax inhibitor could reach up to 80.66 of viscosity reduction of crude oil original viscosity when the weight percentage of EVA, methylcyclohexane (MCH) and para-xylene (PX) were 10.00, 45.78 and 44.22, respectively. PX was used as the asphaltene depressant along with the inhibitor. An optimization study evaluated that the most optimum conditions were found to be 10.00, 40.09 and 49.90 respectively for EVA, MCH and PX. Â© 2019 Malaysian Institute of Chemistry. All rights reserved.